Bandwidth enhancement of dual‐layer patch antenna using low mutual‐coupling near‐field resonant parasiticl elements. Issue 1 (January 2017) - Guo, Li; Tang, Ming‐Chun; Li, Mei; Xiong, Han; Zeng, Xiaoping; Zeng, Qingsheng
ABSTRACT: A pair of face‐to‐face semicircular split‐ring resonators (SSRRs) was utilized to improve the impedance bandwidth of a planar patch antenna. By loading the SSRRs on the superstrate layer, their fundamental resonant modes could be capacitively induced by the radiation patch of the antenna underneath them, respectively. Benefitting from the ultra‐low mutual coupling level between the SSRRs even though their resonant modes are very close to each other, their resonant frequency ranges could be merged with the resonant frequency range from the fundamental mode of the radiation patch to produce a wide fractional impedance bandwidth as high as 4.2% (witnessing 5.16 times enhancement compared with that of a standard patch antenna), even with such a low profile (only 0.052λ0 height). Moreover, the experimental results, which are in good agreement with the simulation values, demonstrated its stable and excellent radiation characteristics, including strict broadside main beams with high polarization purity and large front‐to‐back ratios over the entire operational bandwidth. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:180–186, 2017